Pestalotia truncata en hojas de Avellano (Gevuina avellana) - Peredo, H.=700 1 Aguilar, A.
(En, Es)
Ilus., 4 ref
Keywords: AVELLANA; PESTALOTIA; HOJAS; ENFERMEDADES FUNGOSAS; NECROSIS; CHILE; AGRICULTURA TECNICA